Social Innovation Project The Development Of Kampung Jamu - Chandra, Chelsy; Indrawati, Flavesya Gabriele; Navarro, Navarro; Agrita, Natania (PT. Amirul Bangun Bangsa, 2024)
Kampung Jamu Karang Pilang is already known to several local communities. This Kampung Jamu has been around since the 60s, founded by their ancestors and continued by subsequent generations until today. Nearly 90% of the residents of Kampung Jamu sell herbal drinks, but there are no shops, they only sell them around on motorbikes. For marketing itself, the marketing of Kampung Jamu is not yet extensive. Each seller has their own area to sell, such as in Lakarsantri, Wiyung and the surrounding areas. Kampung Jamu has positive and good potential for development. Therefore, to increase sales of the Kampung Jamu business, we offer marketing training to residents there so that Kampung Jamu can be widely known by herbal connoisseurs. So, they not only get buyers from the surrounding area but also throughout Java because of their social media marketing and utilizing sophisticated technology. From the results of the survey and several considerations, this project was held, namely